Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1063/1.5109320
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-local model-based control of the square-back Ahmed body wake flow

Abstract: This paper presents a new model-free control approach applied to a dynamical fluidic system. The main objective is to evaluate the ability of this closed-loop control technique to control the bistability of a turbulent wake flow past to a square-back Ahmed body. This bistable behavior occurs for some configurations depending mainly on the ground clearance. Due to the unsteady position of the wake vortex cores, the bistable phenomenon is responsible of a strong variation of the lateral force (drift force) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…The / values for DB_0 and DB_35 is comparable to The length of the reverse flow region behind the isolated square back model is L r /H = 1.36. This value is comparable to L r /H = 1.39 reported in previous studies [10,38]. In the presence of a follower, the length of the reverse flow region behind the square back model (L r /H = 1.53) increased by 13%.…”
Section: Streamwise and Wall-normal Mean Velocities In The Wake Regionsupporting
confidence: 87%
“…The / values for DB_0 and DB_35 is comparable to The length of the reverse flow region behind the isolated square back model is L r /H = 1.36. This value is comparable to L r /H = 1.39 reported in previous studies [10,38]. In the presence of a follower, the length of the reverse flow region behind the square back model (L r /H = 1.53) increased by 13%.…”
Section: Streamwise and Wall-normal Mean Velocities In The Wake Regionsupporting
confidence: 87%
“…Moreover, the side-alternating control promotes the vortex shedding dynamics in the wake resulting in a detrimental impact on the drag. Similarly, Brackston et al (2016) with oscillating side flaps and Plumejeau et al (2019) also with pulsed jets have shown similar mixed 2 % drag reduction using similar feedback control with linear control methods. To mitigate the lateral bi-stable dynamics, only passive control methods have proven to be satisfyingly efficient in terms of associated drag reductions.…”
Section: Introductionmentioning
confidence: 80%
“…1 Since the pioneering work of Prandtl about the use of active flow control (AFC) for delaying boundary layer separation, 2 AFC has witnessed a fast growth and has become an increasingly important technology for the pursuit of industrial and sustainable solutions. 3 Prospective applications of AFC to problems of industrial and environmental importance include, to name a few, reducing the aerodynamic drag on aircrafts, 4,5 manipulating the vortex in the wake of bluff bodies, [6][7][8][9][10] and optimizing the design and performance of wind turbines [11][12][13] and gas turbines. 14 Nevertheless, finding efficient strategies for performing AFC remains a challenge.…”
Section: Introductionmentioning
confidence: 99%